Critical literacies, meaning making and new epistemological perspectives (2008)
This article presents a research analysis in which Brazilian university students were the subjects of research in regard to their reading of cinema images. The analysis discusses the way the meanings are constructed by these students and reflects on interpretation and meaning construction in accordance with newepistemological perspectives that have been postulated recently (Morin, 1998; Lankshear and amp; Knobel, 2003). It, thus, considers the present needs of the multimodal and hypertextual communication approached in the multiliteracy studies (Cope and amp; Kalantzis, 2000), and the university  preparation for a critical and participative cultural and social practice (Castells, 1999).Key words: Meaning making, critical literacy, digital epistemologiesEste artículo presenta un análisis investigativo en el cual alumnos de una universidad brasileña fueron entrevistados sobre sus lecturas de imágenes de cine. El análisis discute la manera en que los significados son construidos por estos alumnos y reflexiona sobre la interpretación y la construcción de los mismos, según la nueva perspectiva epistemológica que ha sido postulada recientemente (Morin 1998; Lankshear and amp; Knobel 2003). Considera las necesidades presentes de la comunicación multimodal e hipertextual imbuida en los estudios de multiletramento (Cope and amp; Kalantzis, 2000), como así también la preparación universitaria para una práctica social crítica y participativa (Castels, 1999).Palabras Clave: Creación de significados, lecto-escritura crítica, epistemologías digitales